El impacto de la gestión administrativa - operativa en las asociaciones textiles en la ciudad de Quevedo año 2019 – 2020. plan estratégico para organizaciones textiles de la economía popular y solidaria - Fabre Nicola, Mabel (2021)
The Impact of the administrative - operational management in the Textile Associations of the popular and solidarity economy in the city of Quevedo year 2019 -2020, reflects the weaknesses in the management of administrative processes, formulation of objectives, strategies and procedures; thus also visualize the scarce participation of commercialization in the public and private sector; The research project is justified by finding several weaknesses that the textile associations of the city of Quevedo present, in their administrative - operational part, for which it is intended to design a Strategic Plan, which allows to implement short and long planning term of activities, improve processes, make decisions according to a strategic approach, promote participation in the private sector, offer products from the catalog, contribute to the opening of new markets that allow generating resources so that partners have work and income in an equitable manner, appearing attractive in the participation of the economy and social development. The methodology bases its approach in a qualitative-quantitative and descriptive way, it tries to demonstrate through the historical-logical, inductive, deductive and descriptive methods; the analysis and interpretation of the data, through direct observation, interviews with the directors of the associations and surveys of the members, members of each of the organizations; Interview questionnaires, observation guides, discussion tables and surveys will be used as a collection instrument